2009
DOI: 10.1093/ndt/gfp411
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin for preventing exit-site infection and peritonitis in patients undergoing peritoneal dialysis

Abstract: Mupirocin prophylaxis was effective on preventing ESI and peritonitis due to S. aureus and other organisms in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 21 publications
0
77
1
9
Order By: Relevance
“…S. aureus carriage was also more frequent among poorly controlled patients, in agreement with previous reports (3). Interestingly, the latter condition was not associated an increased risk of peritonitis or TESI, probably because carriers were systematically scrutinized and treated with nasal or pericatheter mupirocin (or both) as needed (25). The association between glycemic control and TESI should not be unexpected, given the correlation between DM and skin and soft-tissue infections, particularly in a surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus carriage was also more frequent among poorly controlled patients, in agreement with previous reports (3). Interestingly, the latter condition was not associated an increased risk of peritonitis or TESI, probably because carriers were systematically scrutinized and treated with nasal or pericatheter mupirocin (or both) as needed (25). The association between glycemic control and TESI should not be unexpected, given the correlation between DM and skin and soft-tissue infections, particularly in a surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic protocols against S. aureus are effective in reducing the risk of S. aureus catheter infections (66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) Routine exit-site care by the patient begins when the exit site is well healed; such care is part of the patient's training. Water and antibacterial soap are recommended by many centers.…”
Section: Exit-site Care To Prevent Peritonitismentioning
confidence: 99%
“…3 As it was shown in the previous studies, the use of prophylactic antibiotics at the exit site or orally (neomycin sulfate, mupirocin, rifampin, TMP-SMX, ciprofloxacin) reduce S. aureus colonization and catheter-related infection rate. [4][5][6][7] In the recent studies, it has been shown that application of mupirocin to the exit site considerably reduces ESI and peritonitis rate. 8,9 Currently, the most popular regimen for mupirocin is to apply it at the exit site once a day, 3-5 times a week.…”
Section: Introductionmentioning
confidence: 99%